INDONESIAN EFL TEACHER’S SELF-EFFICACY AND ONLINE CLASSROOM MANAGEMENT DURING COVID-19 PANDEMIC - Aulia Rahmawati; Yanty Wirza (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2022)
Since the COVID-19 outbreak, online education has been mandated. Many teachers handled it well; others did not. Research has found that successful online teaching was related to the teacher's self-efficacy. Thus, it is vital to investigate EFL teachers' self-efficacy and their ability to manage challenges in online learning. In this qualitative design, the data were collected via questionnaires and interviews. The questionnaires were statistically calculated, and the interview were coded and transcribed. This study revealed that teachers with high and low self-efficacy struggled in managing online classes related to instructional, behavioral, and contextual issues. Furthermore, teachers with high self-efficacy develop more innovative and effective solutions to problems in an online classroom. However, low self-efficacy teachers tend to be inflexible and unconfident when confronted with challenging issues in an online classroom. Then, the findings also indicated that high self-efficacy teachers quickly adapted and resolved difficulties when disruptions aroused. Finally, effective online education is entirely up to the teachers. As a result, teachers needed to be adaptable and more effective in managing online classroom activities. In this regard, teacher education programs should include online classroom management into their curricula and develop strategies for increasing teachers' self-efficacy.Keywords: COVID-19 pandemic, EFL teacher's self-efficacy, online classroom   management